Standards of Judicial Review : Is it Time to Change our Analysis ? - Grey, Julius (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2004)
The notion of a pragmatic and functional analysis has become a mantra in administrative law, producing three technical standards of review, one of which is selected at the start of virtually every case. All technical concepts tend to outlive their utility and, it is suggested that the current one should now be reconsidered. There is no doubt that courts must apply different degrees of judicial deference to various types of decisions. However, just as the old distinction between judicial and administrative acts ceased to be helpful in most matters, without ever totally disappearing, the present categories are losing their utility and, if unmodified, might produce an unduly technical and formalistic system of law. It is, in particular, questionable whether these concepts work well in certain specific fields — in disciplinary law, for example and in disputes involving fundamental rights. The issue of „expertise“ in such matters is far from easy and may often generate injustice.